Lived religion in Latin America: an enchanted modernity - Morello, Gustavo (Oxford scholarship online, 2021)
What does the practice of religion look like in Latin American today? Using semi-structured interviews with 254 individuals in three cities with shifting religious landscapes and different cultural histories, Morello highlights the diversity within Latin America, exploring societies that are understudied and examining a broad array of religious traditions.